Service Quality and INTENTION to Return to the Service of Foreign Tourists to Naka Tour Company in Prabang Capital, Luang Prabang Province - soukhavong, Lah; SIRISACK, Dalivanh; SOUNTHALY, Seng Aloun (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The research aims to 1) examine the travelling characteristics and service quality and repurchase intention of foreign tourists toward the Naga tour in Luang Prabang Capital, Luang Prabang, and 2) investigate the service quality that affects the intention to repurchase among international tourists toward Naga Tour Company in Luang Prabang Capital, Luang Prabang Province. A quantitative research design was applied. Data were collected from 400 foreign tourists with structured questionnaires, and data were analysed using descriptive and inferential statistical methods by multiple regression analysis with the Enter method. The results found that: 1) Examine the travelling characteristics and service quality, and repurchase intention of foreign tourists toward the Naga tour from Thailand, which accounted for 23%. They had visited Luang Prabang for the first time 65.5 % and prefer to travel with a couple/family 40.8 % with total expenses during travelling between 501-1,500 USD/time, with 69.3%. They prefer travelling during high season 62% and find information via social medias 52.3 % with reasons for travelling to the world heritage city is 27.7 %, and friends’ recommendation for choosing Naga tour company’s service 57.8%. 2) Investigate the service quality that affects the intention to repurchase among international tourists toward Naga Tour Company, which consists of five dimensions: tangibles, reliability and trustworthiness, responsiveness to customers, assurance, and empathy. These dimensions of service quality influence tourists’ intention to make repeat purchases with Naga Tour Company and can predict repeat purchase intention for the company at a level of 28.4% at the 0.05 level of statistical significance. The results provide useful information to the company of Naga Tour Company to maintain a plan and seek opportunities to attract tourists to repurchase Naga's services in the future while maintaining service quality standards and improving the company's image and providing better service to foreign tourists.